Personal Correspondence - Abrahams, Peter (My University, 1963)
Letter to Peter Abrahams from J.B. Kelly of the University of Puerto Rico
3 pg. Typed script, sepia-toned, in fairly good condition.
Keywords: Letters; Personal Correspondence